The International Health Regulation 2005 and Indonesia’s Actions in Handling the Covid-19 Outbreak as the State’s Responbility - Noer Indriati; Aryani Yuliantiningsih; Wismaningsih Wismaningsih (Fiat Justisia: Jurnal Ilmu Hukum, 2022)
An increase in international trip results in health risks and problems that can be solved through cooperation between countries and international organizations. This study aimed to analyze legal phenomena using certain methods, systematics, and thoughts juridical and statute approaches. The data were analyzed using the normative-qualitative technique. International Health Regulation 2005 is a legal framework of the World Health Organization (WHO) and soft law that requires no ratification. This regulation forms the basis for achieving global health goals, necessitating compliance from countries in line with Articles 2, 3, and 6 of the 2005 IHR. The State's obligations under national and international law in protecting citizens include respecting and fulfilling government implementations. Furthermore, it is expected to issue several laws and provide health facilities and services. The Government continues to increase various efforts to control the spike in active cases, such as through vaccination programs..